GNSS Remote Sensing of Man‐Made Space Weather Events on Consecutive Days Over East Asia - P. K. Rajesh; C. H. Charles Lin; Susumu Saito; Tzu‐Jui Huang; J. D. Huba; Mitchell M. Shen; Min‐Yang Chou; Jia Yue; Chi‐Yen Lin (Space Weather, 2025)
Abstract The maiden launch of Gravity‐1, labeled as the most powerful all‐solid propellent rocket yet, on 11‐January‐2024 around 0530 UT from an offshore launch platform, Yellow‐Sea, China by OrienSpace was followed by the 48th launch of H‐IIA rocket from Tanegashima space center by Japanese Aerospace Exploration Agency at 0444 UT the next day. These rare launches on consecutive days over similar geographical regions and local‐times yielded rocket‐induced concentric traveling ionospheric disturbances (CTIDs) and depleted total electron content (TEC) by 50%–70% (20–60 TEC units (TECU) reduction). The CTIDs with periods 9–11 min and wavelengths 300–720 km propagated at speeds of 300–1,100 m/s, displaying acoustic dispersion characteristics. The TEC depletions covering a region of 3.5–4.5°, lasted for 60–90 min before eventually recovering. Three‐dimensional Global Ionospheric Specification (GIS) electron density profiles and TEC tomography inversions indicate ionospheric depletions over 250–320 km altitudes. The observed rate of TEC depletions during the two events are used to compare the water molecule (H2O) content in the combustion exhausts of the two rockets by using SAMI2 (SAMI2 is Another Model of Ionosphere) simulations. The results show that Gravity‐1 emitted only 5%–7% of the H2O contained in H‐IIA exhaust, while the rapid occurrence of TEC depletion covering a wider spatial area indicates its steeper vertical (closer to zenith) trajectory. The observations are further used to estimate the possible delay by the TEC gradients by solving the carrier‐phase ambiguity over selected stations. The results indicate a delay gradient of up to 60 mm/km, too small to threaten ground‐based augmentation systems (GBAS).